MEMAKNAI BUDAYA LOKAL DAN GLOBAL DALAM PENGAJARAN BAHASA ASING - Suhaeb, Laelah Azizah S. (English Department FBS UNP, 2010)
Multicultural diversity in Indonesia has become an amazing icon for many other countries which feel envy with the cultural richness of the archipelago. Although the Indonesian culture constantly growing, our civilization must be maintained and kept. Foreign Languages has been recognized in formal and non formal education in Indonesia. Learning and teaching foreign languages is not easy because it does not just teach vocabulary and grammar but also teaches how and when language is used, or in other words, learning the language is also learning culture. Foreign language teaching materials should contain the local culture and the culture of the target language in balanced. Because of the language would be useful if it can be used where the language is required